TEACHING LANGUAGE THROUGH VIRGIL IN LATE ANTIQUITY - Foster, Frances (Classical quarterly, 2017)
Roman magistri and grammatici taught their students a wide range of subjects, primarily through the medium of Latin and Greek literary texts. A well-educated Roman in the Imperial era was expected to have a good knowledge of the literary language of Cicero and Virgil, as well as a competent command of Greek. By the late fourth and early fifth centuries, this knowledge had to be taught actively, as everyday Latin usage had changed during the intervening four centuries. After the reign of Theodosius the division between the Eastern and the Western Empires meant that knowledge of Greek was no longer as common as it had once been in the West. At the same time, by Late Antiquity, migration increased and foreigners as well as provincials moved within the empire, for example, in search of military promotion. There is evidence that recruitment to official or public careers was based less on birth than on education. These ambitious newcomers sent their children to Roman schools, which would facilitate their access to public office. Receipt of this education provided a means by which men from less privileged backgrounds could achieve promotion to such office and become prominent and influential individuals. At the same time a late Roman education also produced a high level of cultural homogeneity among those who had experienced it. So what might we learn about how language was taught—and what kinds of language were valued—in a late-antique Roman school? How might this contribute to our understanding of late-antique Roman elite society?